The Implementation of Health Education Interventions to Improve Family Knowledge about Pain Management in Gout Arthritis - Ani Nuraeni (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
Gout arthritis is a condition characterised by recurrent attacks of the joints accompanied by crystal deposits. Age, gender, medical history, obesity, diet, and alcohol are the main factors of gout arthritis. Pain management is one strategy used to prevent gout. But few clients are informed of how to apply pain management, thus health education is required to improve client awareness. The goal of this case study is to determine the degree of knowledge before and after receiving health education about pain management. It does this through a descriptive technique using a pretest and posttest design. Data collection used a questionnaire on 2 subjects who had been diagnosed with gout arthritis. The results of the case study showed an increase in family knowledge after being given health education, namely subject 1 scored 48% (low knowledge) to 88% (good knowledge), while subject 2 scored 60% (sufficient knowledge) to 80% (good knowledge). This case study recommends the importance of health education to families with gout arthritis on a scheduled basis which is carried out by health workers